Effect of low-temperature conditioning combined with methyl jasmonate treatment on the chilling resistance of eggplant (Solanum melongena L.) fruit - Shi, Junyan (J Food Sci Technol, 2019)
Chilling injury (CI) can injure harvested eggplants and lead to a reduction in postharvest quality. The present study examined the effect of low-temperature conditioning (LTC) combined with a methyl jasmonate (MeJA) treatment on CI by analyzing the visual appearance and physiology of eggplants stored at 4 °C. Results indicated that treatment of eggplants with LTC + MeJA effectively maintained the visual quality of eggplants, inhibited a decline in chlorophyll and total phenolics, delayed the accumulation of malondialdehyde (MDA), decreased polyphenol oxidase (PPO) gene expression and enzyme activity, and enhanced the activity of the antioxidant enzymes, catalase (CAT) and peroxidase (POD), as well as the expression of their corresponding genes. Collectively, the data indicate that LTC combined with MeJA effectively improves the CI tolerance of postharvest eggplant fruit stored at 4 °C, by enhancing the activity and relative gene expression of antioxidant enzymes.